Marketing Up the Wrong Tree? Organisational Perspectives on Attracting and/or Retaining Older Adults in Sport - Jenkin, Claire; van Uffelen, Jannique G. Z.; O'Sullivan, Grant; Harvey, Jack; Eime, Rochelle M.; Westerbeek, Hans (Frontiers in Sports and Active Living, 2021)
Community sport is seen as a suitable setting for physical activity for different population groups. Older adults (aged 50+ years) are a rapidly growing population group. Physical activity is critical for healthy ageing, however sport participation rates for older adults are very low. The aim of this study was to investigate how sporting organisations perceive sport for older adults. This cross-sectional study surveyed 171 representatives from Australian National and State Sporting Organisations. Descriptive statistics were used to summarise the results and the three sporting organisation categories’ (high, medium and low participation) responses were compared using non-parametric statistics. Contextualised in the perspective of organisational change, a framework for marketing to the ageing consumer was used to interpret the results. Older adults are not a high priority group for most sporting organisations, however the benefits of engaging older adults were recognised, particularly in context of increasing participation numbers. A lack of age-appropriate programmes was perceived to be a major barrier of engaging older adults. This lack of programmes stems from older adults being deemed as a less attractive segment than other age groups for sporting organisations. Modifications that sports felt they could make to attract and/or retain older adults included specific marketing and age appropriate opportunities. There was widespread consensus across sporting organisations, suggesting that perceptions of older adult sport participation were comparable across the sector, such as increasing participation numbers and engaging their older fan base. In the context of attracting, and retaining, older adults in sport clubs, it was concluded that most sporting organisations are not (yet) ready to build ‘age friendly’ sporting environments. There is very limited literature on the organisational perspective of older adults and sport, meaning this study is unique in the field. Although sport policy encourages organisations to grow their participation, most organisations do not actively and strategically engage older adults. This research provides an understanding of why this untapped market is not a priority target and provides comprehensive insights for policy makers to better engage with this population group.